From Classroom to Online Lessons: Adapted Methodology for Teachers - Corbi, Alberto; Burgos, Daniel (Lecture notes in educational technology, 2021)
Any private teacher, school, college, or academic institution might suddenly be challenged to move from an onsite (face-to-face) methodology to an online one. This drastic, dramatic change can happen overnight, as proven by the response to the rapidly spreading Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), commonly known as COVID-19. Between March and April 2020, around half of the world’s educational institutions found themselves closing their doors and completely shutting down all conceivable classroom activities. Fortunately, educators found their way around this partial suspension by swiftly switching to an online format. This entailed moving their classes from the typical face-to-face setting over to the Internet, overnight. For the most part, teachers could count on the help and technical support of their home institutions. Sometimes, however, teachers felt somehow forced to figure out by themselves how to carry out such a colossal transition. Independently of the path taken, it is worth dissecting and analysing this type of contingency, the associated undertaken procedures, adopted strategies, and even the necessary stage tricks as well. In this article, we summarise the educational standards related to e-learning and review the theoretical background and research literature around online teaching. We also present the most recent advances in the aforementioned fields. It may seem that the methodologies associated with classroom and online teaching do not have much in common but, as we will show, there are plenty of overlapping areas and large bits of knowledge that can be transferred from the former to the latter. In the few cases where this is not possible, we also itemise the possible solutions.
Keywords: face-to-face education; online learning; confinement; LMS; virtual classroom; lab and group activities; online exams; Scopus(2)